(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
Existential therapy places a lot of emphasis on death. And it takes much of its thinking from Martin Heidegger’s reflections on the subject in Being and Time. This paper will discuss Heidegger’s phenomenological analysis of how we experience death, will attempt a critique of this view and will explore how Jacques Derrida’s more recent writings about death (across various texts but with particular reference to The Gift of Death), might take our thinking in new directions.